Cost-energy modelling and profiling of smart domestic grids. (2016) - Gentile, Ugo; Marrone, Stefano; Mazzocca, Nicola; Nardone, Roberto
The growing academic and industrial interest in Smart Grids raises the need for methods and techniques supporting the choice of best-saving strategies in intelligent home devices. This paper presents a model-based approach for the integrated evaluation of the energy billing profiles by using the formalism of fluid stochastic Petri nets, able to capture both continuous and discrete system aspects. The prime feature of the modelling approach is the compositionality by which a modeller can easy customise the overall configuration as well as the inner behaviour of a system. This paper also proves the feasibility of the approach by analysing three different saving policies in a Domestic Smart Grid environment and comparing the simulation results.